The cultural divide in Europe: migration, multiculturalism, and political trust - McLaren, Lauren M. (Cambridge Universisty Press, 2012)
One of the defining features of modern states is their incorporation of notions of political and social community based on shared language, history, and myths. However, large numbers of citizens in modern states have come to believe their national communities are under threat from several modern forces, including immigration. Using the European Social Survey (2002-2009), this paper explores the extent to which perceived threats posed by large-scale immigration undermine national political communities by reducing trust in national politicians and political institutions. The findings indicate that even after controlling for other predictors of trust in the political system, concerns about the effect of immigration on the national community have an impact on trust in politics. Moreover, having a lengthy post-war history with mass immigration mediates this effect, while the potentially mobilizing effects of far-right parties on the relationship between concern about immigration and political distrust are somewhat limited.